Bekele Desta and M. Lunga: Analyzing Determinants of Construction Project Resilience and Success in Ethiopia: a Structural Equation Modelling Approach (PLS-SEM). International Journal of Engineering and Management Sciences. doi: 10.21791/IJEMS.2026.03 - Bekele Desta, Kebede; Lunga, Msengana (International Journal of Engineering and Management Sciences, 2026)
In the original publication, the authors identified three errors.